PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT TELKOM INDONESIA Tbk PERIODE 2013-2022 - Wahyuni, Sri; Jamaludin (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the Current Ratio, Debt to Equity Ratio and Earning Per Share (EPS) on the share price of PT Telkom Indonesia Tbk, both partially and simultaneously. The independent variables used in this research are Current Ratio, Debt to Equity Ratio and Earning Per Share (EPS) while the dependent variable used in this research is Share Price. The research method used in this research is an associative quantitative method. The type of data used in this research is secondary data. The population in this research is the financial reports of PT Telkom Indonesia Tbk for the period 2013-2022. The sample used in this research is the balance sheet, profit and loss report and an overview of the share prices of PT Telkom Indonesia Tbk for the period 2013-2022. The data analysis techniques used are descriptive analysis test, classical assumption test, multiple linear regression test, hypothesis test and coefficient of determination test with the SPSS version 22 application. The results of the study show that partially the Current Ratio has no significant effect on stock prices where tcount is -0.170 < ttable 2.44691 with a significant value of 0.871 > 0.05. Partially, the Debt to Equity ratio has no significant effect on share prices, where t is -0.652 < ttable 2.44691 with a significant value of 0.538 > 0.05. Partially Earning Per Share has a significant effect on Share Prices, where tcount is 2.920 > ttable 2.44691 with a significant value of 0.027 < 0.05. Simultaneously the Current Ratio, Debt to Equity Ratio and Earning Per Share do not have a significant effect on share prices, where the Fcount value is 3.667 < Ftable 4.76 with a significant value of 0.082 > 0.05.